Analisis Saham-Saham Jakarta Islamic Index untuk Membentuk Portofolio yang Optimal dengan Menggunakan Single Indeks Model Studi Kasus Pada Bursa Efek Jakarta. - Sutarti, Sutarti (Jurnal Ilmiah Ranggagading (JIR), 2007)
The purpose of this research is to find out shares of Jakarta Islamic Index (JII) those are considered as selected shares at optimal portfolio by using Single Index Model and to find out fund allocation of selected shares at optimal portfolio as well as to find out expected return and deviation standard of return at optimal portfolio. Counting result of optimal portfolio formation and Single Index Model shows tat the difference between using Rf in counting and using assumption of Rf = 0 is extremely insignificant. To be viewed from expected return and variance, there is difference as high as 0,0047 or 0,47%. That is why, Single Index Model can be utilized as analysis instrument for Muslim investor or reksadana syariah in determining optimal portfolio. Keywords: Single Index Model; Investment; Optimal portfolio